Manifestasi Islam Sosialis Dalam Tradisi Keagamaan Masyarakat Dusun Sumberejo - Saepudin, Saepudin; Laprassani, Mutia; Lailisia, Zahara; Dirham, Muhammad; Arahman Zainalputra, Surya; Wulandari, Tasanur; Komala Dewi, Cantika (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
In this article, the researcher examines the manifestation of socialist Islam in religious traditions that discuss the relationship between Islamic teachings and the concept of socialism concerning customs in the Sumberejo hamlet community, and how the two can synergize to create an egalitarian society. In this context, the author argues that the Islamic values ​​taught by the Prophet Muhammad SAW, who opposed the exploitative capitalist structure. Through an analysis of the thoughts of figures such as Muhammad Hatta and HOS Tjokroaminoto, this journal highlights how Islamic teachings can be interpreted to support social justice and shared welfare. The author also emphasizes the importance of reconstructing Islamic theology to return to the principles of liberation, which can overcome social and economic inequality in society. By referring to verses of the Qur'an and critical thinking about capitalism, this journal invites readers to reflect on how Islamic teachings can be applied in a modern context to achieve the goals of inclusive and just socialism. Through this approach, it is hoped that a collective consciousness will be created that encourages positive and sustainable social change. This research is a type of qualitative research with an ethnographic approach. As a supporting tool, the author in this study uses The results of this study are to determine the social values ​​in the process of implementing the Friday Kliwon, Yasinan, Pengajian, and Suroan traditions in Sumberejo Hamlet.